2015
DOI: 10.1038/ni.3309
|View full text |Cite
|
Sign up to set email alerts
|

Interferon and IL-27 antagonize the function of group 2 innate lymphoid cells and type 2 innate immune responses

Abstract: Group 2 innate lymphoid cells (ILC2 cells) are type 2 cytokine-producing cells of the innate immune system with important roles in helminth infection and allergic inflammation. Here we found that tissue-resident ILC2 cells proliferated in situ without migrating during inflammatory responses. Both type I and type II interferons and interleukin 27 (IL-27) suppressed ILC2 function in a manner dependent on the transcription factor STAT1. ILC2-mediated lung inflammation was enhanced in the absence of the interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

32
403
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(437 citation statements)
references
References 44 publications
32
403
1
1
Order By: Relevance
“…Interestingly, we identified ILCs both locally and in the periphery in patients with BCa and observed a skewing toward a group 2 ILC phenotype that was associated with a worsening of the disease. A recent study reported that murine tissue-resident ILC2 expand locally in inflammatory conditions (45). Accordingly, bladder tumors and intravesical BCG stimulation may favor ILC2 proliferation/ induction in the bladder, as supported by in vitro data.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, we identified ILCs both locally and in the periphery in patients with BCa and observed a skewing toward a group 2 ILC phenotype that was associated with a worsening of the disease. A recent study reported that murine tissue-resident ILC2 expand locally in inflammatory conditions (45). Accordingly, bladder tumors and intravesical BCG stimulation may favor ILC2 proliferation/ induction in the bladder, as supported by in vitro data.…”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that ILC2s express a number of chemokine receptors, including CCR2, CCR4, CCR5, and CXCR4 under certain conditions. In particular, CXCR4 is only expressed in ILC2s after exposure to IL-33 [37]. RNA transcriptome analysis of intestinal ILC2s has also revealed transcripts for CCR8 and its ligand CCL1 [38].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with our observation that IL-27 has an immunoprotective role in Th2-mediated disease allergic asthma. Very recent studies provided evidence that IL-27 as well as type I and type II IFNs are able to suppress group 2 innate lymphoid cell responses in vitro and in vivo (38,40) and suggested that this mechanism is next to IFN-g induction in importance for the immunoregulation via IL-27 of type 2 immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…This heterodimeric cytokine binds to the IL-27 receptor and gp130 to activate STAT1 (33)(34)(35) and induce Th1 cell differentiation (32,36) whereas it directly suppresses Th2 and Th17 differentiation (37). Very recently, it was shown in different models of lung inflammation, including allergic inflammation and viral respiratory tract infection, that IFNs and IL-27 regulate the function of group 2 innate lymphoid cells and thereby together restrict type 2 immune responses (38)(39)(40). Using a model of immune perturbation, Molofsky et al (41) have also shown that a counterregulatory mechanism involving IFN-g and IL-33 is involved in regulating type 2 innate lymphoid cells and thereby maintenance of immune homeostasis.…”
mentioning
confidence: 99%